MODEL KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI - vivi nila sari; Marta Widian Sari; Monica Rini; Dian Aggraini; Andry Novrianto (J-MIND (Jurnal Manajemen Indonesia), 2022)
This study aims to determine how big the influence of Organizational Culture and Organizational Climate on Organizational Commitment through Job Satisfaction as an Intervening Variable at PT. Aditya Prima Utama. This research consists of independent variables, namely Organizational Culture and Organizational Climate and Organizational Commitment and Job Satisfaction as Intervening Variables. The analytical method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3. The method of data collection in this study is to use a questionnaire filled out by respondents, namely employees of PT. Aditya Prima Utama. The results of data analysis concluded (1) There is a positive and significant effect of organizational culture on job satisfaction at PT. Aditya Prima Utama. (2) There is a positive and significant influence of organizational climate on job satisfaction at PT. Aditya Prima Utama. (3) There is a positive and significant influence of organizational culture on organizational commitment at PT. Aditya Prima Utama. (4) There is a positive and significant influence of organizational climate on organizational commitment at PT. Aditya Prima Utama. (5) There is no significant effect of job satisfaction on organizational commitment at PT. Aditya Prima Utama. (6) Job satisfaction cannot mediate the influence of organizational culture on organizational commitment at PT. Aditya Prima Utama. (7) Job satisfaction cannot mediate the influence of organizational climate on organizational commitment at PT. Aditya Prima Utama.